COMMON SIZE ANALYSIS AT PT ADARO ENERGY INDONESIA TBK BEFORE AND DURING COVID – 19 - Baniady Gennody Pronosokodewo; Nur Ika Yuliastuti; Sri Suryaningsum (CV. Fahr Publishing, 2023)
The global health crisis in the form of the Covid-19 pandemic has a major impact on national economic activities and the global economy. The Covid-19 phenomenon is very influential on companies - large to small companies. This analysis uses the common size method. This method is very helpful in reading financial statements. Changes that occur in the statement of financial position or profit and loss can be detected quickly and permanently. The study intends to analyze the financial performance of PT Adaro Energy Indonesia Tbk before and during Covid-19 using the common size analysis method. In this study, the technique of comparative descriptive analysis between years was used. The research uses annual report data. The data used is the time range from 2018 to 2021.The results of the analysis of the research show (1) the company's short-term financial condition in terms of current assets did not experience significant changes in 2018- 2021. (2) short-term financial conditions seen from current liabilities tended to increase during the year, on the contrary, long-term liabilities decrease. (3) For equity from 2018 to 2019 and from 2020 to 2021, it has decreased but is still around 59%. (4) Common size analysis of PT Adaro Energy Indonesia's income statement shows that the percentage of net profit to operatingincome will increase in 2021 to 25.7%.